Experimental Analysis of Hybrid Panels Combining Flax/PLA Composite with UHMWPE and Steel Under Ballistic Impact - Liu Jiao-Wang; Samuel Charca; Borja Valverde; J.A. Loya; Carlos Santiuste (Journal of Natural Fibers)
This study investigates the feasibility of substituting UHMWPE and steel with flax/PLA green composite in ballistic applications with the objective to increase sustainability and cost-effectiveness. Results reveal that flax/PLA composite exhibits significantly lower ballistic performance than UHMWPE due to its lower energy absorption capacity. However, hybrid panels where 33% of UHMWPE was replaced by biocomposite showed similar values of V50 than homogenous UHMWPE, suggesting potential for partial replacement without compromising ballistic performance. However, the hybrid panels of biocomposite and steel showed a ballistic limit much lower than pure steel. Analysis of scan results indicates distinct failure modes: UHMWPE exhibits viscoelastic deformation, biocomposites show local damage failure, and steel displays ductile behavior. These findings provide insights into the viability of hybridizing UHMWPE with biocomposites for eco-friendly ballistic applications.